IMPLEMENTASI SISTEM PEMBAYARAN DIGITAL MENGGUNAKAN QRIS PADA UMKM RM PADANG SIKEMBAR - Lawrance Sitanggang; Grace Sitompul; Euodia Eneas; Stefanieka Damayanti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to implement a QRIS-based digital payment system at RM Padang Sikembar, an MSME located in West Bandung, to enhance transactional efficiency and reduce cash dependency. The methodology employed was direct assistance (field mentoring), encompassing problem identification, socialization of benefits, QRIS integration, and operational training. The findings revealed that prior to implementation, the business relied solely on cash transactions, posing a risk of losing customers who prefer digital payment methods. Following the adoption of QRIS, the transaction process became more practical, rapid, and flexible, allowing consumers to pay via various mobile banking and e-wallet applications. Ultimately, QRIS implementation improved customer convenience and supported the modernization of payment systems within the MSME sector,with an increase in consumer and sales reaching approximately 30%.